Estudo dos efeitos cardiovasculares da quitosana sulfatada em ratos normotensos - Silva, Luziane Gomes (2022)
Natural polymers are generally easy to obtain, safe, non-toxic, biocompatible, biodegradable and found in abundance in nature. Chitosan is an N-deacetylated polysaccharide derived from chitin, found in exoskeleton components of crustaceans and insects, as well as in some cell walls of bacteria and fungi. The introduction of sulfate groups (SO42-) in the chitosan chain can reduce its thrombogenic property, since this modification makes it with a negative surface charge, which causes the electrostatic repulsion of negatively charged blood proteins. Sulfated chitosan is a kind of heparin-like polysaccharide and its higher degree of sulfated compared to other natural sulfated polysaccharides promotes great interest in its study and applicability. The development of new biomaterials using chitosan as a raw material boosts the research field and makes it attractive to the pharmaceutical industry. This has been corroborated by the increase in the number of studies and scientific publications in recent years based on the interaction of chitosan with the biological system. However, there are still no data regarding the cardiovascular effects of sulfated chitosan administered systemically. The proposed project aims to study the cardiovascular effects of sulfated chitosan in normotensive rats. In the present study, the cardiovascular effects of sulfated chitosan were evaluated, using in vivo approaches to assess MAP and HR in normotensive rats and an in vitro approach in rats' thoracic aorta artery rings. As main results, it was observed that sulfated chitosan induced bradycardia and hypotension at the doses administered in anesthetized normotensive rats. The effect of chitosan was presented in two phases. The first phase, called P1, corresponds to the rapid response phase. And the second phase, named here as P2, is the recovery phase for the initial value, or close to it, the injection of sulfated chitosan. The two phases of chitosan effect were seen both with the vagus nerve intact and after bilateral vagotomy. With regard to heart rate, chitosan induced a mild tachycardia after treatment with L-NAME and in mean arterial pressure chitosan doubled its hypotensive response compared to normotensive rats. And in in vitro studies, chitosan induced vasodilation in aortic rings, not depending on the integrity of the endothelial layer to induce relaxation. In tissue preparations maintained under basal tonus, sulfated chitosan does not show a significant response, that is, it does not show any type of vascular effect.